Lactococcus lactis D4 Restores Gut Microbiota Balance in Azoxymethane and Dextran Sulfate Sodium-induced Colorectal Cancer Rat Model - Suswita, Rini; Rivai, Muhammad Iqbal; Iqbal, Muhammad; Irwan, Irwan; Suchitra, Avit (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Gut microbiota plays a crucial role in the initiation and progression of colorectal cancer (CRC), with various bacterial species including Lactococcus lactis implicated in this process. However, there is a lack of studies reporting the specific effects of L. lactis on microbiota balance in the context of CRC, especially strain D4. Therefore, this study was conducted to evaluate the effect of L. lactis D4 administration on gut microbiota balance in a rat model of CRC.METHODS: This experimental study involved Sprague Dawley rats that were separated into untreated control (CO group), CRC-induced (CA group), and L. lactis D4-treated CRC-induced (LLD group). The CRC induction was performed by giving azoxymethane (AOM) and dextran sulfate sodium (DDS). Gut microbiota profile was analyzed using next generation sequencing (NGS), and microbial community dynamics were assessed through alpha and beta diversity metrics.RESULTS: L. lactis D4 restored gut microbiota balance by regulating Firmicutes/Bacteroidota ratio, and changing the microbiota composition by increasing the number of bacteria from the phylum Actinobacteria and decreasing bacteria from the phylum Bacteroidota and Proteobacteria. Alpha diversity was reduced in the LLD group, suggesting a decreased bacterial diversity post-treatment, but more closely aligned with the CO group than the CA group. Beta diversity analysis showed that the microbial composition of the treated group was similar to the CO group, while the CA group exhibited a distinct microbiota profile, characterized by higher abundance of pathogenic bacteria and reducing beneficial microbial species.CONCLUSION: L. lactis D4 administration effectively modulates gut microbiota in CRC model, enhancing the presence of beneficial bacteria from the Firmicutes and Bacteroidota phylum while suppressing pathogenic species from the Proteobacteria phylum.KEYWORDS: colorectal cancer, gut microbiota, next generation sequencing, Lactococcus lactis D4